2017
DOI: 10.1111/wre.12244
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach to control glyphosate‐resistant Ambrosia trifida with tillage and herbicides in glyphosate‐resistant maize

Abstract: Glyphosate-resistant Ambrosia trifida is a competitive and difficult-to-control annual broad-leaved weed in several agronomic crops in the Midwestern United States and Ontario, Canada. The objectives of this study were to compare treatments for control of glyphosate-resistant A. trifida with tillage followed by pre-emergence (PRE) and/or post-emergence (POST) herbicides in glyphosate-resistant maize and to determine the impact of A. trifida escapes on maize yield. Field experiments were conducted in 2013 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 33 publications
1
28
2
Order By: Relevance
“…This research confirms that spring tillage can be an effective weed control tool for herbicide‐resistant giant ragweed, especially when used in conjunction with other effective weed control strategies (Ganie et al, 2016, 2017). Of the treatments evaluated, the 14 days post‐emergence onset treatment was optimal, achieving 54% control of giant ragweed while minimizing potential yield reductions due to delayed planting of corn or soybean.…”
Section: Useful Conversionssupporting
confidence: 75%
See 1 more Smart Citation
“…This research confirms that spring tillage can be an effective weed control tool for herbicide‐resistant giant ragweed, especially when used in conjunction with other effective weed control strategies (Ganie et al, 2016, 2017). Of the treatments evaluated, the 14 days post‐emergence onset treatment was optimal, achieving 54% control of giant ragweed while minimizing potential yield reductions due to delayed planting of corn or soybean.…”
Section: Useful Conversionssupporting
confidence: 75%
“…Giant ragweed emergence was reduced the week following tillage when tillage occurred early, which provides additional time for post‐emergence weed control operations. This research suggests that delayed pre‐plant tillage and planting can be effectively used as part of an integrated weed management plan to control herbicide‐resistant giant ragweed (Ganie et al, 2016, 2017).…”
Section: Useful Conversionsmentioning
confidence: 99%
“…Therefore, to avoid overdependence on these herbicide mixtures and ensure an effective use of multiple-resistant crop technology without enhancing the evolution of multiple herbicide-resistant weeds, an integrated weed management approach for GR giant ragweed or other weed species should be implemented. Recently, integrated weed management approaches involving preplant tillage followed by PRE and/or POST herbicides with multiple modes of action have been developed for the effective management of GR giant ragweed in maize and soybean (Ganie et al, 2016, 2017). Future studies should consider the evaluation of these herbicide mixtures for the control of other prominent GR weed species including common ragweed, common waterhemp, horseweed, kochia ( Kochia scoparia L.), and Palmer amaranth in Nebraska.…”
Section: Resultsmentioning
confidence: 99%
“…Management of giant ragweed has become complicated due to its extended emergence pattern in the eastern maize belt of the United States (Schutte et al, 2008, 2012) and due to the evolution of giant ragweed biotypes resistant to ALS-inhibitors and/or glyphosate in the Midwestern United States (Johnson et al, 2006; Norsworthy et al, 2010, 2011; Jhala et al, 2014; Kaur et al, 2014). Nevertheless, effective integrated management options for GR giant ragweed based on preplant tillage followed by PRE and/or POST applications of herbicide-mixtures have been reported in maize and soybean (Ganie et al, 2016, 2017). Recent research in Nebraska has reported that giant ragweed is sensitive to synthetic auxin herbicides and can be effectively controlled by a preplant application of 2,4-D (Jhala et al, 2014; Kaur et al, 2014; Ganie et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In its native habitats, giant ragweed generally occurs in early-successional and disturbed sites with moist soils (Bassett & Crompton, 1982), although it also occurs in drier upland sites (Regnier et al, 2016). Giant ragweed is also a problematic agricultural weed that causes substantial crop losses when not controlled early in the season (Barnett & Steckel, 2013;Ganie et al, 2017;Harrison, Regnier, Schmoll, & Webb, 2001;Webster, Loux, Regnier, & Harrison, 1994) and that has been found to have multiple instances of herbicide resistance (Heap, 2018). It has been a management concern for farmers in the Eastern Corn Belt for at least the past 30 years, but more recently it has been undergoing range expansion in both agricultural and successional habitats farther west and north into the Great Plains where the climate is drier and cooler and where historical agricultural practices differ (Regnier et al, 2016).…”
Section: Introductionmentioning
confidence: 99%